Sample pretreatment method for in-situ analysis of impurities in high-purity quartz sand

The pre-treatment of high-purity quartz sand samples is simplified by methods such as oil immersion observation and epoxy resin inlay, and the problems of long testing cycle and high cost of high-purity quartz sand analysis in the existing technology are solved, and the rapid and accurate sample screening and in-situ are achieved. analyze.

CN119164728APending Publication Date: 2024-12-20ZHENGZHOU MINERALS COMPOSITIVE UTILIZATION RES INST CHINESE GEOLOGICAL ACAD

Patent Information

Application Number
CN202411205394.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art has problems with long periods and high cost in the analysis and testing of impurities in high-purity quartz sand. The conventional sample pretreatment methods cannot meet the in-situ analysis requirements of high-purity quartz resources, especially the ineffective screening of suitable products. The samples were subsequently analyzed in situ.

Method used

Use oil immersion observation method to select quartz single mineral particles with less gas-liquid inclusions, and simplify the target preparation process through epoxy resin inlay, polishing, cleaning and other steps to avoid secondary contamination, and ensure the representative sample and the surface to be tested. effective exposure.

Benefits of technology

Fast and effective pretreatment of high-purity quartz sand samples is achieved, ensuring the data accuracy of subsequent in-situ analysis and the representativeness of samples, simplifying the target preparation process, and reducing costs and time overhead.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119164728A_ABST
    Figure CN119164728A_ABST
Patent Text Reader

Abstract

The invention provides a sample pretreatment method for in-situ analysis of impurities in high-purity quartz sand, which comprises the following steps: crushing, screening, scrubbing, desliming and grading a raw ore sample to obtain a mineral with the particle size of-2mm + 0.5 mm; carrying out quartz single mineral selection on minerals with the particle size of + 0.5 mm by adopting an optical microscope; the method comprises the following steps: uniformly dispersing selected quartz single minerals on a glass slide, and preparing an oil-immersed sheet; placing the oil immersed sheet under a polarizing microscope, selecting quartz single mineral particles with low gas-liquid inclusion content, and cleaning and drying the quartz single mineral particles; and embedding the quartz single mineral particles into epoxy resin, polishing and cleaning to obtain the high-purity quartz sand sample target sheet. According to the method, an oil immersion observation method is firstly adopted to select quartz single minerals with relatively low gas-liquid inclusion content, so that the sample representativeness of subsequent in-situ analysis test is ensured; then, epoxy resin is adopted for embedding, polishing and cleaning, target material preparation is simplified, and secondary pollution to a to-be-detected surface is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of quartz in-situ analysis, in particular to a sample pretreatment method for in-situ analysis of impurities in high-purity quartz sand. Background Art

[0002] The different contents and distribution characteristics of impurity elements such as Al, Ti, Li, K, and Na in high-purity quartz sand have a great impact on its downstream applications, but the current analytical testing methods all evaluate the quality of high-purity quartz sand based on the content characteristics of impurity elements, and the evaluation results are somewhat one-sided. At the same time, the sample to be tested must be a high-purity quartz sand product after mineral processing and impurity removal-chemical purification, which leads to a long judgment cycle and high cost. For this reason, exploring a rapid raw material-end high-purity quartz evaluation method is of great significance for the rapid screening of high-purity quartz resources. Laser ablation-inductively coupled plasma mass spectrometry, as an excellent sample in-situ detection equipment, is widely used in the in-situ analysis of inorganic elements of various solid samples and liquid samples. In-situ analysis of general solid samples can be carried out by cutting the solid sample into a suitable size or preparing the solid sample into a target material, and then placing it in a laser ablation cell for sample analysis. However, for high-purity quartz samples, specific minerals and specific erosion surfaces need to be selected, and the target making process must also fully consider the secondary contamination of the surface to be tested by various media in the process. Therefore, the conventional sample pretreatment process does not meet the technical requirements for in-situ analysis of impurity elements in high-purity quartz resource raw materials.

[0003] Chinese patent document CN113340780 A discloses a method for detecting the content of fluid inclusions in high-purity quartz. The method adopts the sand sample thin section preparation method specified in the standards such as "Technical Specifications for Rock and Mineral Identification Part 2: Rock Thin Section Preparation DZ / T0275.2-2015" to prepare high-purity quartz sand into sand thin sections. The steps are cumbersome, requiring steps such as gluing and grinding to obtain the observation surface to be tested. At the same time, the high-purity quartz sand is glued and solidified after preparation, and can only be used to observe the development of inclusions. Sample screening is impossible, resulting in the inability to screen suitable samples for subsequent in-situ analysis. Summary of the invention

[0004] The present invention proposes a sample pretreatment method for in-situ analysis of impurities in high-purity quartz sand. The method firstly adopts an oil immersion observation method to select quartz single mineral particles with less gas-liquid inclusion content to ensure the representativeness of the samples for subsequent in-situ analysis and testing; then epoxy resin is used for inlaying, polishing and cleaning, which greatly simplifies the target material preparation process and avoids secondary contamination of the surface to be tested during the target preparation process.

[0005] The technical solution of the present invention is achieved as follows: A sample pretreatment method for in-situ analysis of impurities in high-purity quartz sand comprises the following steps:

[0006] (1) crushing and screening the raw ore sample to obtain a crushed product with a particle size of -2 mm, scrubbing, desludging and classifying the crushed product to obtain a mineral with a particle size of +0.5 mm;

[0007] (2) using an optical microscope to select single quartz minerals with a particle size of +0.5 mm; evenly spreading the selected single quartz minerals on a glass slide, covering it with a cover glass, and dripping immersion oil on one end of the cover glass to obtain an oil-immersion slide;

[0008] (3) placing the oil-immersed slide under a polarizing microscope, selecting quartz single mineral particles whose gas-liquid inclusion area accounts for less than 10% of the particle area, and washing and drying the finally selected quartz single mineral particles;

[0009] (4) The quartz single mineral particles dried in step (3) are embedded in epoxy resin, and then polished and cleaned to obtain a high-purity quartz sand sample target.

[0010] Furthermore, in step (4), the method of embedding the quartz single mineral particles in the epoxy resin is as follows:

[0011] 1) placing the quartz single mineral particles dried in step (3) into anhydrous ethanol, ultrasonically cleaning them, and then purging and drying them with low-pressure N2 of 0.2Mpa-0.4Mpa;

[0012] 2) sticking a double-sided tape to the mold, arranging the quartz single mineral particles dried in step 1) on the double-sided tape under an optical microscope, and then purging with N2;

[0013] 3) After mixing the epoxy resin and the coagulant in proportion, pour the mixture into the mold of step 2), and then let it stand at room temperature to solidify. The mold is removed to obtain a quartz sample embedded in the epoxy resin.

[0014] Furthermore, in step (4), the polishing and cleaning methods are as follows:

[0015] Use a polishing cloth made of acetate fiber satin woven fabric and a water-based diamond suspension as a polishing liquid to perform deep polishing on the quartz sample after epoxy resin embedding in step 3), and the duration of deep polishing is set to 3-5 minutes;

[0016] Then, a polishing cloth made of porous chloroprene rubber and a non-drying fumed silica suspension are used as a polishing liquid to perform oxidation polishing on the deeply polished quartz sample. The duration of oxidation polishing is set to 1-3 minutes.

[0017] The quartz sample after oxidation polishing is cleaned with ultrapure water to remove the polishing liquid; then it is placed in ultrapure water and ultrasonically cleaned; finally, the quartz sample is taken out and purged and dried with 0.2Mpa-0.4Mpa low-pressure N2 to obtain a high-purity quartz sand sample target.

[0018] Furthermore, in step (2), immersion oil is dripped onto one end of the cover glass, and the immersion oil gradually penetrates into the quartz particles between the cover glass and the slide glass until there are no bubbles between the quartz particles.

[0019] Furthermore, in step (1), the method for scrubbing and desludging the crushed product is as follows:

[0020] Add the crushed product with a particle size of -2mm into the vertical stirred mill, adjust the slurry concentration to 40%-60%, add Na2CO3 as a cleaning agent at a mass ratio of 2%-5%, set the speed of the vertical stirred mill to 500-800r / min, and the stirring and scrubbing time to 20-40min; after scrubbing, the mineral product is screened to remove the -0.1mm ore mud.

[0021] Beneficial effects of the present invention:

[0022] The oil immersion observation method adopted by the present invention is easy to operate, can observe the type and distribution of inclusions in a targeted manner, and can select high-purity quartz particles in real time, and select quartz single mineral particles with less gas-liquid inclusion content for subsequent in-situ analysis, thereby ensuring that the subsequent analysis and test data effectively reflects the presence of impurity elements in the quartz crystal.

[0023] Different from conventional target material preparation, the target material preparation method adopted in the present invention does not require coarse grinding and fine grinding, which greatly simplifies the target material preparation process and effectively ensures that the test surface of the quartz single mineral particle is fully exposed, ensuring that the sample pretreatment is time-saving and efficient.

[0024] The high-purity quartz target sample prepared by this method can fully ensure that the test surface is the test surface selected in the early stage. After subsequent in-situ analysis, the representative information of trace elements in the quartz lattice in the effective regional high-purity quartz sample can be obtained. The conventional method is to randomly disperse the sample and then settle it on the target surface, and then polish and expose it. It cannot guarantee the effectiveness of the test surface. The measurement result is likely to be interfered by the mineral inclusions and gas-liquid inclusions in the sample, resulting in large errors in the final measured high-purity quartz lattice impurity element information. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 It is a schematic diagram of the high-purity quartz sand sample target piece of the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] A sample pretreatment method for in-situ analysis of impurities in high-purity quartz sand comprises the following steps:

[0029] (1) For different types of high-purity quartz ores, such as granite pegmatite, white granite, quartzite, vein quartz, etc., jaw crusher and roller crusher are used to crush the blocky ores in turn, and 2mm sieve is used for screening. Products larger than 2mm are returned to the roller crusher for crushing until they are all crushed to -2mm. After the -2mm products are mixed and shrunk, the crushed products with a particle size of -2mm are obtained.

[0030] There is a lot of mineral mud adhering to the surface of various minerals in the -2mm crushed product, which needs to be removed by scrubbing and desludging. Add the -2mm crushed product to the vertical stirred mill, adjust the pulp concentration to 40%-60%, add Na2CO3 as a cleaning agent at a mass ratio of 2%-5%, set the speed of the vertical stirred mill to 500-800r / min, and the stirring and scrubbing time to 20-40min; after scrubbing, the mineral product is repeatedly screened with a 0.10mm sieve until all the -0.1mm mineral mud is removed, and the product on the sieve is processed in the next step.

[0031] Since laser ablation has certain requirements on the particle size of the quartz single mineral to be measured, the mineral products after scrubbing and desludging are graded and repeatedly screened using a 0.50mm sieve. Minerals with a particle size of -0.5mm are temporarily stored as fine products, and mineral products with a particle size of +0.5mm are processed in the next step. The selection of a particle size of +0.5mm can fully guarantee the sufficient erosion surface for subsequent determination of single mineral in-situ data.

[0032] (2) Use an optical microscope to select quartz single minerals from mineral products with a particle size of +0.5 mm, and select quartz single minerals that are completely dissociated; then take a glass slide, wipe it clean with soft paper, take a few quartz single mineral particles with a particle size of +0.5 mm and place them in the center of the glass slide, paying attention to spreading them evenly;

[0033] Place a small cover glass on the quartz particles, use a dropper to absorb a small amount of immersion oil such as olive oil, and drip it along the edge of the cover glass. Wait for the immersion oil to gradually penetrate into the quartz particles between the cover glass and the slide until there are no bubbles between the particles, thus obtaining an oil immersion slide.

[0034] (3) placing the prepared oil-immersion slide under a polarizing microscope, adjusting the objective lens magnification and light intensity to the required level under transmitted light conditions, observing the development characteristics of inclusions in the quartz, and selecting quartz single mineral particles with a small content of gas-liquid inclusions, such as selecting quartz single mineral particles in which the area of ​​gas-liquid inclusions accounts for less than 10% of the particle area; repeatedly washing the finally selected quartz single mineral with ultrapure water, and drying in a clean oven.

[0035] For millimeter-scale solid particle mineral samples (quartz single mineral after treatment in step (3)), in order to meet the sampling requirements of the laser ablation system, the millimeter-scale solid particle mineral samples need to be embedded in epoxy resin to make quartz sample target pieces. Through the fixation of particles, target making, and polishing and cleaning of the target pieces, the surface of the quartz particle samples in the target pieces is made flat and smooth, ensuring that the amount of quartz sample ablated each time under the same laser ablation conditions is the same, reducing the detection error caused by different injection amounts, thereby improving the accuracy of the detection results.

[0036] (4) Place the quartz single mineral to be tested in an acid- and alkali-resistant beaker (such as a polytetrafluoroethylene beaker), add anhydrous ethanol to the beaker, and ultrasonically clean the quartz particles in the beaker for 5 minutes. Then take out the quartz single mineral and purge and dry it with 0.2Mpa-0.4Mpa low-pressure N2. By cleaning the surface of the quartz sample, the interference of impurities introduced during sampling and transportation on the test results can be removed.

[0037] Cut the double-sided tape to appropriate size and stick it to the cold mounting mold. Arrange the selected quartz single mineral on the double-sided tape under an optical microscope, and then perform the single mineral particle mounting work after N2 purging.

[0038] Epoxy resin and epoxy resin coagulant were mixed in a weight ratio of 3:1, and the mixture of epoxy resin and epoxy resin coagulant was slowly poured into a cold mounting mold. The cold mounting mold was placed in a Class 100 clean fume hood and allowed to stand at room temperature for 24 hours to solidify the epoxy resin in the cold mounting mold. The cold mounting mold was then removed to obtain a quartz sample embedded in epoxy resin.

[0039] Using a polishing cloth made of acetate fiber satin woven fabric and a stable water-based diamond suspension as the polishing liquid, the epoxy resin-embedded quartz sample was deep polished for 3-5 minutes, and then a polishing cloth made of porous chloroprene rubber and a non-drying fumed silica suspension as the polishing liquid were used to oxidize the high-performance polished quartz sample for 1-3 minutes. The two polishings made the sample surface smooth and clean, preparing for subsequent laser ablation.

[0040] The polished quartz sample target was rinsed with ultrapure water to remove the polishing liquid, then placed in a beaker, added with ultrapure water, and ultrasonically cleaned for 15 minutes. After taking out the sample, it was purged and dried with 0.2Mpa-0.4Mpa low-pressure N2 to complete the preparation of the sample target.

[0041] The high-purity quartz sample target prepared according to the above steps is shown in the schematic diagram. Figure 1 shown.

[0042] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A sample pretreatment method for in-situ analysis of impurities in high-purity quartz sand, characterized in that: The following steps are involved: (1) crushing and screening the raw ore sample to obtain a crushed product with a particle size of -2 mm, scrubbing, desludging and classifying the crushed product to obtain a mineral with a particle size of +0.5 mm; (2) using an optical microscope to select single quartz minerals with a particle size of +0.5 mm; evenly spreading the selected single quartz minerals on a glass slide, covering it with a cover glass, and dripping immersion oil on one end of the cover glass to obtain an oil-immersion slide; (3) placing the oil-immersed slide under a polarizing microscope, selecting quartz single mineral particles whose gas-liquid inclusion area accounts for less than 10% of the particle area, and washing and drying the finally selected quartz single mineral particles; (4) The quartz single mineral particles dried in step (3) are embedded in epoxy resin, and then polished and cleaned to obtain a high-purity quartz sand sample target.

2. The sample pretreatment method according to claim 1, characterized in that: In step (4), the method of embedding the quartz single mineral particles in the epoxy resin is as follows: 1) placing the quartz single mineral particles dried in step (3) into anhydrous ethanol, ultrasonically cleaning them, and then purging and drying them with low-pressure N2 of 0.2Mpa-0.4Mpa; 2) sticking a double-sided tape to the mold, arranging the quartz single mineral particles dried in step 1) on the double-sided tape under an optical microscope, and then purging with N2; 3) After mixing the epoxy resin and the coagulant in proportion, pour the mixture into the mold of step 2), and then let it stand at room temperature to solidify. The mold is removed to obtain a quartz sample embedded in the epoxy resin.

3. The sample pretreatment method according to claim 2, characterized in that: In step (4), the polishing and cleaning methods are as follows: Using a polishing cloth made of acetate fiber satin woven fabric and a water-based diamond suspension as a polishing liquid, the quartz sample after epoxy resin embedding in step 3) is deep polished, and the time for deep polishing is set to 3-5 minutes; Then, a polishing cloth made of porous chloroprene rubber and a non-drying silica gel suspension are used as the polishing liquid to perform oxidation polishing on the deeply polished quartz sample. The oxidation polishing time is set to 1-3 minutes. The quartz sample after oxidation polishing is cleaned with ultrapure water to remove the polishing liquid; then it is placed in ultrapure water and ultrasonically cleaned; finally, the quartz sample is taken out and purged and dried with low-pressure N2 of 0.2Mpa-0.4Mpa to obtain a high-purity quartz sand sample target.

4. The sample pretreatment method according to claim 1, characterized in that: In step (2), immersion oil is dripped onto one end of the cover glass, and the immersion oil gradually penetrates into the quartz particles between the cover glass and the slide glass until there are no bubbles between the quartz particles.

5. The sample pretreatment method according to claim 1, characterized in that: In step (1), the method for scrubbing and desludging the crushed product is as follows: Add the crushed product with a particle size of -2mm into the vertical stirred mill, adjust the slurry concentration to 40%-60%, add Na2CO3 as a cleaning agent at a mass ratio of 2%-5%, set the speed of the vertical stirred mill to 500-800r / min, and the stirring and scrubbing time to 20-40min; after scrubbing, the mineral product is screened to remove the -0.1mm ore mud.

Citation Information

Patent Citations

  • Method for detecting content of fluid inclusion in high-purity quartz

    CN113340780A

Cited By

  • Method for measuring particle size coefficient

    CN120314158A